Redefining global entrepreneurship : shifting focus from China to Central and Eastern Europe - Vaduva, Sebastian; Brouthers, Lance; Benchis, Melisa; Nedelcut, Amalia Cristina (Emerald, 2024)
Purpose The purpose of this paper is to explore the viability of shifting foreign direct investment (FDI) from China to Central and Eastern European (CEE) countries in light of recent geopolitical and economic challenges. By analyzing case studies, it argues that CEE nations offer a compelling alternative for Western European businesses, with stronger intellectual property protection, political stability and alignment with European Union (EU) sustainability goals. The paper provides insights for firms and policymakers on mitigating risks and enhancing business operations by pivoting toward the CEE region, offering practical recommendations for adapting to shifting global trade dynamics. Design/methodology/approach The design methodology uses the case study approach to analyze the shift of FDI from China to CEE. This method examines the geopolitical, economic and legal contexts influencing business decisions, using real-world examples of Western European companies that have made this transition. The case studies highlight key factors in decision-making and the benefits of relocating investments to the CEE region. Findings The study identifies several advantages of the CEE region over China for Western European firms. These include geographic proximity, similarities in business values and purposes, environmental accountability, trustworthiness in business, enforceable noncompetition rules, lower risks of counterfeiting, reduced political and administrative risks, lower risks of intellectual property theft and reduced risks of negative publicity. Practical implications The findings suggest that Western European firms should consider redirecting their FDI to the CEE region to mitigate risks associated with investing in China. This move could offer long-term benefits despite short-term complications. Originality/value This paper contributes to the FDI theoretical framework by enhancing the cultural, administrative, geographic and economic (CAGE) distance framework. It provides a unique perspective on the shifting dynamics between Europe and China and highlights the potential of the CEE region as a viable alternative for FDI.
Keywords: China; European Union; CEE; Businesses; FDI; fi=Julkisjohtaminen|en=Public Management|